EFEK SAKIT GIGI TERHADAP KONSENTRASI BELAJAR PADA MURID-MURID SEKOLAH DASAR PENGUNJUNG KLINIK GIGI RUMAH SAKIT ZAINUL ABIDIN BANDA ACEH: EFFECT OF TOOTHACHE ON LEARNING CONCENTRATION OF ELEMENTARY SCHOOL CHILDREN IN ZAINUL ABIDIN HOSPITAL BANDA ACEH - Armasastra Bahar (Dentika: Dental Journal, 2010)
Dental caries is one of the most prevalent chronic diseases which are mostly common in children. Learning ability and concentration in children could be interfered due to caries and dental pain. The purpose of this study was to determine the effect of toothache toward learning concentration of elementary school children. The subjects of this study were 95 elementary school students in Banda Aceh taken from the children who came to the Dental Clinic at Zainul Abidin General Hospital in Banda Aceh with the condition of dental pain. Dental pain threshold was measured by anamnesis and Wong-Baker Faces Scale rating, and their learning concentration was measured by Trial Making Test Method introduced by Reyton. The relationship of dental pain with learning concentration was analyzed by Kruskal Wallis. The result showed that children with very painful threshold needed 66,44 seconds for completing TMT A and 66,78 seconds for TMT B, followed by moderate painful threshold needed 45,36 seconds for completing TMT A and 49,26 seconds for TMT B and less painful threshold needed 25,39 seconds for completing TMT A and TMT B 30,62 seconds. In conclusion there was a significant relations (p<0.05) beetween toothache and learning concentration among elementary school children in Banda Aceh